Work-Related Stressors in Employees Presenting with Musculoskeletal Disorders - Chetty, Laran (British Journal of Healthcare and Medical Research, 2024)
Background: The purpose of this project was to evaluate work-related stressors in employees presenting with musculoskeletal disorders using the Management Standards for Work-Related Stress survey proposed by the Health and Safety Executive (HSE) at an occupational health service. Methods: An OPAS-G2 database was utilised to identify and select employees with musculoskeletal disorders that attended the occupational health service within the data collection period. Employees were mailed the HSE survey and asked to complete and return it in a pre-paid envelope. Results: The standards Demands, Managers’ Support, Relationships and Role were in the red category while Control, Peer Support and Change were in the yellow category. Conclusion: The stressors associated with musculoskeletal disorders were not being optimally managed. An organisational strategy to tackle work-related stressors should be developed and implemented as a matter of high priority.